Políticas de inovação educacional: subjetivação e modo de ser docente na escola plural - Jose Cosme Drumond (2011)
The object of this thesis is a study the positive and negative subjective processes constituting the mode of being a teacher in the movement of educational innovation as a policy implemented in Brazil from the 1990. To carry out the research was chosen Plural School, educational innovation policy implemented in Belo Horizonte, in 1994, and our study fixed between the emergence of politics and the year 2000, considered in this research as the period of deployment the same. For purposes of this study, educational innovation is seen as a movement implemented in schools or educational systems in order to create new ways to organize and implement curricula and educational practices. These movements intent on overcoming the traditional perspective on education reform since its purpose is to produce alternatives to sustain innovative practices within schools, changing the organization of time and space in curriculum practices, resulting in new intersubjective relations in classrooms and in institutional spaces. The teacher is the main agent of innovation policy in education and teachers should incorporate its principles and take responsibility for their enforcement practice. The main hypothesis is that the difficulties in understanding the proposal, the assignment of new meanings in contextualizing school policy would produce the same transformation of the discourse, and, consequently, spraying some of the speeches included in the text of the policy. The methodological approach was characterized by studying the case of the School Plural. To carry out the analysis we practice articulated investigative movements. From the approach of educational policies built by Ball (1992, 1994) and called the continuous cycle of education policy, we analyze the contexts of influence and policy text by Plural School, to visualize the production of political discourses and their possible effects on teachers. From writing for the production of effective policy guidance and dialogue with the literature of the area and production on the Plural School, discussed the process of subjectification teaching, in implementing the policy and its possible consequences on the effectiveness of it. The completion of the work highlights the importance that acquire the subjective processes in which teachers are placed in the Plural School, if such a policy of educational innovation, and that result in difficulties to carry out the politics as it was designed. It is clear that for policy implementation, it is necessary to establish a way of being a teacher, which results in specific practices. Also emphasizes that the processes of contextualization with the adhesion and resistance of school workers are crucial to the effectiveness or otherwise of the policies of educational innovation and has consequences on how to be teachers